2016
DOI: 10.1155/2016/8017571
|View full text |Cite
|
Sign up to set email alerts
|

Does Hsp60 Provide a Link between Mitochondrial Stress and Inflammation in Diabetes Mellitus?

Abstract: The focus of this review is to summarise the known relationships between the expression of heat shock protein 60 (Hsp60) and its association with the pathogenesis of Type 1 and Type 2 diabetes mellitus. Hsp60 is a mitochondrial stress protein that is induced by mitochondrial impairment. It is known to be secreted from a number of cell types and circulating levels have been documented in both Types 1 and 2 diabetes mellitus patients. The biological significance of extracellular Hsp60, however, remains to be est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 59 publications
1
48
0
Order By: Relevance
“…HSP60 is involved in the prevention of heat-induced protein damage and the transportation and refolding of cellular proteins from the cytoplasm into the mitochondrial matrix (29; 30). Additionally, studies have indicated a role of HSP60 in several disorders where the relevance of the vitamin D endocrine system has been discussed, including stress response, diabetes, cancer and certain types of immunological disorders (30)(31)(32)(33). It can be speculated that HSP60 may be involved in the putative transportation of VDR from cytoplasm to mitochondrial matrix.…”
Section: Resultsmentioning
confidence: 99%
“…HSP60 is involved in the prevention of heat-induced protein damage and the transportation and refolding of cellular proteins from the cytoplasm into the mitochondrial matrix (29; 30). Additionally, studies have indicated a role of HSP60 in several disorders where the relevance of the vitamin D endocrine system has been discussed, including stress response, diabetes, cancer and certain types of immunological disorders (30)(31)(32)(33). It can be speculated that HSP60 may be involved in the putative transportation of VDR from cytoplasm to mitochondrial matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Manuscript to be reviewed Heat shock proteins (HSPs) are a type of cellular companion protein produced by biological cells that are stimulated by environmental stressors and can be divided into several families, each of which is composed of different members (Juwono & Martinus, 2016;Craig, 2018;Pearl et al, 2008;Tang et al, 2005;Bolhassani & Rafati, 2008) (Table 3). HSPs can be internalized by APCs through receptor-mediated endocytosis and can also promote the activity of some cytokines, chemokines, and co-stimulatory molecules through the NF-B signaling pathway, since HSPs are the molecular chaperones of the antigen epitopes in the APC-MHC I delivery pathway (Robert, 2003;Zachova et al, 2016).…”
Section: Heat Shock Proteins (Hsps)mentioning
confidence: 99%
“…On the other hand, serum HSP60 has been recognized as a potent inductor of proinflammatory mediators in various cells indulging innate immune cells, skeletal muscle, cardiomyocytes, and adipocytes [11,[15][16][17]. Furthermore, the high levels of serum HSP60 have been found in the individuals with adjuvant arthritis and atherosclerosis [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, accumulating evidences have linked HSP60 with diabetes mellitus and diabetic complications, although the molecular mechanisms are poorly understood [18][19][20]. For instance, serum HSP60 levels have been found to be significantly elevated in the patients with type 2 diabetes and morbid obesity, due to enhanced mitochondrial stress and responsible for inflammation [20][21][22].…”
Section: Introductionmentioning
confidence: 99%